Association of ABO Blood Groups and Rh factor with COVID-19 Infection in the Population of Rawalpindi Region - Ali Murad Jamal , Hafiz Abu Safian , Ather Iqbal , Bilawal Abbas , Umer Irshad , Junaid Azhar, Ali Murad Jamal , Hafiz Abu Safian , Ather Iqbal , Bilawal Abbas , Umer Irshad , Junaid Azhar (Journal of Rawalpindi Medical College, 2021)
Background: COVID-19 caused by the SARS-CoV-2 virus has resulted in a worldwide pandemic. Around 1.6 million mortalities have been reported worldwide due to its fatal impacts on the human body and no specific treatment is yet available. Thus, this study was planned to determine the relationship between different blood groups and COVID-19 infection according to age and gender in the population of the Rawalpindi region. Materials and Methods: Around 3000 RT-PCR tests for SARS-CoV-2 were carried out in a private lab in Rawalpindi from April to June 2020, according to which 1160 (38.66%) people tested positive by RT-PCR. Data was collected from all positive individuals using a proforma containing demographic details and blood groups. Data were analyzed using SPSS v. 23.0 (Armonk, NY: IBM Corp.). Results: Out of 1160 COVID-19 positive participants, 594 (51.2%) were males, and 566 (48.8%) were females. Age group 51-60 years was the most prevalent among COVID-19 infected population. Those having blood group B-positive have a higher chance of getting infection i.e. 45.6% (n=529), and blood group AB-negative have the least prevalence i.e. 0.34% (n=4). Overall, Rh-positive blood types are higher among positively infected populations compared to Rh-negative blood types. Conclusion: Blood group B positive is highly prevalent in COVID-19 positive individuals as compared to other blood groups. Individuals with Rh-positive blood type are frequently infected as compared to those with Rh-negative blood type. These findings should be taken into consideration while managing patients of COVID-19.